Uma proposta de protocolo de normas e legislações para a concepção de projetos arquitetônicos de instituições públicas de ensino: o caso do campus Unila - Butske, Francieli (2018)
Building projects must satisfy their customers and users, which represent functional, aesthetic, comfort and desires and needs, and must comply with a series of requirements for the use and performance of the product, which are established by technical and legal parameters, linked to the standards and legislation. Public education institutions seek through the projects of their campuses an integration between several design elements, ie buildings, open spaces, circulation routes, parking lots, green areas and infrastructure, as well as the specific characteristics of a teaching institution, which involves aspects such as teaching, research, extension, its technical staff and the problems of administration of this universe. The development of these projects is subject to relevant municipal, state and federal laws, technical norms and project recommendations, and does not always follow the pace given by government policies, since the technical teams of universities are, in general, small close to the demand and, pressed by political will, rector's decisions, bidding deadlines and government projects, can hardly organize themselves in the medium and long term. Due to these demands, this paper presents a proposal for a protocol containing norms, laws and other regulations required for architectural design of buildings with a focus on public educational institutions, whose limitations are related to the tight deadlines for the elaboration of the projects, linked to the bidding processes and compliance with annual budgets, to the university master plan, of the rules of accessibility, sustainability, efficiency, quality and economics, using as a case study a federal public university, UNILA, which represents a demand for projects of all academic infrastructure. The application of the protocol contributed to the acceleration of the initial stages of the architectural project development activities carried out by the institution's technical team and considered an important tool for the university's architects, as it collaborated with the accomplishment of the physical and budgetary planning of the institution, daily and future demands to the projects of the university infrastructure of this and other public educational institutions.